Identification of the periodontal ligament material parameters using response surface method. (April 2023) - Song, Yang; Gao, Jinglan; Qi, Chenxi; Liu, Dehai; Xiang, Hongbiao; Zhang, Mian; Yang, Xiuping; Zhang, Chunqiu
Highlights: Elastic modulus, Poisson's ratio, temperature of the periodontal ligament affected the biomimetic degree of finite element simulation. Established Prony series viscoelastic finite element model based on the relaxation experiment. Proposed a method: response surface method and finite element inverse analysis method. Identify the material parameters of the periodontal ligament by Box–Behnken design. Abstract: The orthodontic treatment can be guided by the finite element (FE) simulation of periodontal ligament (PDL) mechanical properties, and the biomimetic degree of FE simulation can be primarily affected by the material properties of the PDL. According to the principle of parameter inverse, a method: response surface (RS) method and FE inverse method were proposed to identify the material parameters of PDL. The Prony series viscoelastic FE model was established based on the relaxation experiment. With root mean square error of simulation results and experimental results as the objective function, the optimal parameter combination was obtained by RS method, and the FE simulation result were compared with the experimental result. The result showed that the optimal parameters of the PDL were elastic modulus: 3.791 MPa, Poisson's ratio: 0.42, temperature: 29.294°C separately, and the simulation result of optimal combination maintained consistency with experiment with the correlation coefficient of 0.97258, indicating that the method proposed in this paper could well identify of PDL material parameters. The parameter identification method used in this paper can significantly improve the calculation efficiency, and reduce the parameter identification error compared with the simple FE inverse method, which has scientific significance and theoretical value.